Guiding of emulsion droplets in microfluidic chips along shallow tracks defined by laser ablation - Rashid, Zeeshan; Coskun, Umut Can; Morova, Yagiz; Morova, Berna; Bozkurt, Asuman Asikoglu; Erten, Ahmet; Jonas, Alexandr; Akturk, Selcuk; Kiraz, Alper (SPRINGER HEIDELBERG, 2017)
We demonstrate controlled guiding of nanoliter emulsion droplets of polar liquids suspended in oil along shallow hydrophilic tracks fabricated at the base of microchannels located within microfluidic chips. The tracks for droplet guiding are generated by exposing the glass surface of polydimethylsiloxane (PDMS)-coated microscope slides via femtosecond laser ablation. The difference in wettability of glass and PDMS surfaces together with the shallow steplike transverse topographical profile of the ablated tracks allows polar droplets wetting preferentially the glass surface to follow the track. In this study, we investigate guiding of droplets of two different polar liquids (water/ethylene glycol) with and without surfactant suspended in an oil medium along surface tracks of different depths of 1, 1.5, and 2 mu m. The results of experiments are also verified with computational fluid dynamics simulations. Guiding of droplets along the tracks as a function of the droplet composition and size and the surface profile depth is evaluated by analyzing the trajectories of moving droplets with respect to the track central axis, and conditions for stable guiding are identified. The experiments and numerical simulations indicate that while the track topography plays a role in droplet guiding using 1.5-and 2-mu m deep tracks, for the case of the smallest track depth of 1 ae m, droplet guiding is mainly caused by surface energy modification along the track rather than the presence of a topographical step on the surface. Our results can be exploited to sort passively different microdroplets mixed in the same microfluidic chip, based on their inherent wetting properties, and they can also pave the way for guiding of droplets along reconfigurable tracks defined by surface energy modifications obtained using other external control mechanisms such as electric field or light.
Keywords: T-JUNCTION; MANIPULATION; MICROCHANNEL; SIMULATION; Science & Technology - Other Topics; Instruments & Instrumentation; Physics